The role of perinatal maternal symptoms of depression, anxiety and pregnancy-specific anxiety for infant's self-regulation: a prospective longitudinal study - Schwarze, Cornelia E.; Heiden, Sina von der; Wallwiener, Stephanie; Pauen, Sabina (Journal of affective disorders, 2024)
Background - Maternal symptoms of anxiety and depression are highly prevalent during pregnancy and postpartum and have the potential to impact fetal development and offspring behavior. However, research on the effects of fetal exposure to maternal subclinical affective symptoms on infant self-regulation is still lacking. Self-regulation provides a fundamental precondition for healthy development and overall life success whereas dysfunctional self-regulation can lead to behavioral problems, poor academic achievement, social rejection, and physical/mental disorders. During pregnancy and infancy, children largely depend upon their mothers in order to successfully regulate their internal states. Given the high prevalence of mothers suffering from anxiety and depressive symptoms during pregnancy and after childbirth, the aim of the present study is to explore how maternal affective symptoms change during the pre- and postnatal period, and how measures obtained in pregnancy and beyond impact self-regulation in infants, as indicated by crying-, sleeping-, and/or feeding problems. - Methods - This prospective longitudinal study investigates the effects of maternal symptoms of depression, anxiety, and pregnancy-specific anxiety on infant's self-regulation in N = 225 mother-infant dyads. Maternal affective symptoms were examined at five prenatal and three postnatal time-points using the Edinburgh Postnatal Depression Scale (EPDS), the State-Trait Anxiety Inventory (STAI) and the Pregnancy Related Anxiety Questionnaire Revised (PRAQ-R2). Infant's self-regulation was assessed twice - at the age of three and six months - using the Crying Feeding Sleeping Scale (SFS). - Results - Maternal pregnancy-specific anxiety was the most significant predictor for infant self-regulatory problems. It predicted crying-, sleeping, and feeding problems and explained up to 18 % of the variance. Even when controlling for maternal postpartum affective symptoms, pregnancy-specific anxiety remained a significant predictor for infant self-regulation problems. - Limitations - Rather homogenous sample (high socioeconomic status). Data based on maternal reports of infant behavior. - Conclusions - Our results suggest that fetal exposure to maternal affective symptoms - specifically pregnancy-related anxiety - plays a substantial role in the development of infant self-regulation problems, potentially mediated by epigenetic modifications. Importantly, even though maternal symptoms of depression and anxiety only reached subclinical levels, they were predictive for infant crying-, sleeping-, and feeding problems. Our findings underline the importance of early prevention and clearly tailored interventions during pregnancy and postpartum to prevent adverse outcome for mother, child and family.
Online verfügbar: 12. Oktober 2023, Artikelversion: 15. November 2023